On this Day : The History of the World in 366 Days - Contributors Addison, Keith [et al.] (London Bounty Books, 2010)
A day-by-day collection of over 8000 events, trivia, quotations, news in brief items, anniversaries and birthdays for every day of the year. Packed full of historical information, this is a book that can be read from cover to cover or dipped into for fascinating facts or special dates such as anniversaries or birthdays. With a whole page for each day of the year and more than 700 illustrations, this newly revised and updated edition of On This Day covers events throughout history day by day. Newspaper-style articles recount all the main stories of the day, from the fall of the Roman Empire to the rise of Mikhail Gorbachev, from the discovery of gravity to landing on the moon, from Beethoven to the Beatles. This book also includes extracts from diaries, letters and speeches, amusing events and trivia that maybe didn't quite make the headlines, famous people's birthdays and a news-in brief column
Include Illustration and Index
Keywords: History -- World history -- Chronology, Historical